2014
DOI: 10.1111/acer.12479
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Biases in Estimating the Relationship Between Alcohol Consumption and Breast Cancer: The Role of Drinker Misclassification Errors in Meta‐Analytic Results

Abstract: Background While alcohol consumption has been linked to breast cancer in women, few studies have controlled for possible biases created by including former or occasional drinkers in the abstainer reference group. We explored the potential for such misclassification errors as sources of bias in estimates of the alcohol-breast cancer relationship. Methods Meta-analyses of population case-control, hospital case-control, and cohort studies to examine relationships between level of alcohol use and breast cancer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 40 publications
0
27
0
2
Order By: Relevance
“…In the case of breast cancer, this bias leads to a small but significant downward shift in the RR estimates which is caused by the misclassification of occasional drinkers (including people who reduce their alcohol consumption due to declining health [Liang and Chikritzhs, 2013] and people who are in better health than are lifetime abstainers due to factors unrelated to alcohol consumption [Stockwell et al, 2012]). The misclassification of former drinkers was not found to affect estimates of the risk of breast cancer (Zeisser et al, 2014); however, the finding that measuring lifetime alcohol consumption leads to a higher breast cancer RR when compared to measuring more recent alcohol consumption supports the hypothesis that former drinker misclassification bias is a factor when measuring the RR between alcohol and breast cancer. Reference group bias also affects the alcohol-attributable breast cancer estimates presented in the meta-analysis by Bagnardi and colleagues (2015), which meta-analysis does not account for this bias and, thus, the alcohol-attributable burden estimates presented in this study can be seen as a conservative estimate of the actual burden of alcohol-attributable breast cancer.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In the case of breast cancer, this bias leads to a small but significant downward shift in the RR estimates which is caused by the misclassification of occasional drinkers (including people who reduce their alcohol consumption due to declining health [Liang and Chikritzhs, 2013] and people who are in better health than are lifetime abstainers due to factors unrelated to alcohol consumption [Stockwell et al, 2012]). The misclassification of former drinkers was not found to affect estimates of the risk of breast cancer (Zeisser et al, 2014); however, the finding that measuring lifetime alcohol consumption leads to a higher breast cancer RR when compared to measuring more recent alcohol consumption supports the hypothesis that former drinker misclassification bias is a factor when measuring the RR between alcohol and breast cancer. Reference group bias also affects the alcohol-attributable breast cancer estimates presented in the meta-analysis by Bagnardi and colleagues (2015), which meta-analysis does not account for this bias and, thus, the alcohol-attributable burden estimates presented in this study can be seen as a conservative estimate of the actual burden of alcohol-attributable breast cancer.…”
Section: Discussionmentioning
confidence: 66%
“…Most of the systematic reviews included in this study are affected by reference group bias (Zeisser et al, 2014). In the case of breast cancer, this bias leads to a small but significant downward shift in the RR estimates which is caused by the misclassification of occasional drinkers (including people who reduce their alcohol consumption due to declining health [Liang and Chikritzhs, 2013] and people who are in better health than are lifetime abstainers due to factors unrelated to alcohol consumption [Stockwell et al, 2012]).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as with other diseases related causally to alcohol consumption, the relative risks for cancer are dependent upon the systematic search strategy, inclusion and exclusion criteria, reference group (and if this includes former drinkers) of the underlying studies 172, 173, 174, use of case–control and/or cohort studies 175 and use of categorical or continuous estimates for alcohol consumption 169 (for relative risk graphs see 176 and Supporting information, Appendix S2). …”
Section: Resultsmentioning
confidence: 99%
“…While many unidentified and uncontrolled factors or biases may have confounded the relationships of interest in these studies, an additional concern is that former and occasional drinkers may be misclassified into the abstaining reference group. Previous studies have showed that such misclassification can bias estimates of health risks from alcohol use, for example, underestimating risks from low–volume drinking [14–19]. Former and occasional drinkers may include people who have stopped or reduced their drinking as they aged and experienced declining health [16, 20].…”
Section: Introductionmentioning
confidence: 99%